Profile of Junior High School Students' Creative Thinking Abilities in Solving Open-Ended Problems on Number Patterns Material - Romadani, Moh. Nafis Husen; Basri, Hasan (Universitas Negeri Surabaya, 2024)
Learning in the 21st century must be transformed from traditional to modern learning. This change is necessary to equip students with 21st-century skills, known as the 4Cs (Communication, Collaboration, Critical Thinking, Creativity). One of the skills thatstudents must master in the 21st century is creativity or creative thinking skills. Creative thinking skills are essential for all students to master at every level of education. This study aims to describe the profile of junior high school students' creative thinking skills insolving open-ended problems in the number pattern material. Creative thinking is the ability to express original ideas, while open-ended questions are problems or questions that have many correct answers. Fluency, flexibility, and novelty are the indicators of creative thinking skills used. The method used in this study is to use a descriptive methodwith a qualitative approach. Data collection in this study was carried out by giving a test about the ability to think creatively. After the creative thinking ability test, three subjects with high, medium, and low creative thinking abilities were selected for the interview. Then the results of the interviews will be analyzed using the time triangulation method.The results of this study concluded that subjects with a high category of creative thinking abilities, subject fulfilled the three indicators of fluency, flexibility, and novelty. In subjects with the medium category of creative thinking ability, it was found that subjectsonly met the indicators of fluency and flexibility. Meanwhile, subjects with low-category creative thinking abilities found that students did not meet the three indicators of creative thinking ability.